A method for preparing primary titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid

By pre-activated grinding and hydrochloric acid decomposition of vanadium titanium magnetite iron slag, combined with leaching, calcium precipitation, roasting and hydrolysis steps, rutile-type titanium dioxide is prepared, which solves the problems of low titanium resource utilization and environmental pollution, and achieves the Efficient recycling of titanium resources and comprehensive utilization of by-products have been reduced, and production costs and environmental pollution have been reduced.

CN116002751BActive Publication Date: 2024-12-24PANZHIHUA QUANRUI IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310060280.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-08
Filing Date
2023-01-16
Publication Date
2024-12-24
Estimated Expiration
2043-01-16

AI Technical Summary

Technical Problem

In the prior art, there are problems of high cost, high pollution and low resource utilization in the production process of titanium dioxide, especially in the treatment of vanadium titanium magnetite iron slag, which is difficult to achieve effective titanium resource recycling and by-products. Comprehensive utilization.

Method used

By pre-activated grinding of vanadium titanium magnetite iron slag, selective decomposition using low-concentration hydrochloric acid, titanium and other impurity elements were separated, and leaching, calcium precipitation, roasting and hydrolysis were followed by steps such as leaching, calcium precipitation, roasting and hydrolysis to prepare rutile titanium. White powder and hydrochloric acid recycling reduce production costs and environmental pollution.

Benefits of technology

The utilization rate of titanium resources has been improved, the application field of by-products has been expanded, the cost of titanium dioxide production of hydrochloric acid method has been reduced, the environmentally friendly production process has been achieved, and the resource utilization rate of vanadium titanium magnetite iron slag has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116002751B_ABST
    Figure CN116002751B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid. The rutile titanium dioxide for pigment is produced by using vanadium-titanium magnetite ironmaking slag, thereby improving the resource utilization rate of titanium in vanadium-titanium magnetite, expanding the application field of by-products, and solving the environmental protection and resource waste problems caused by the storage of vanadium-titanium magnetite ironmaking slag at the current stage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium dioxide and titanium dioxide production, and in particular to a method for preparing primary titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid. Background Art

[0002] Titanium dioxide (titanium dioxide) is the best and most commonly used white pigment at present. It is one of the most important inorganic chemical products and is widely used in coatings, plastics, papermaking, electronics, rubber, ink, chemical fiber, ceramics and other industrial fields. However, the current high-titanium content resources and the limited production of titanium-rich raw materials have restricted the further development of the titanium dioxide production industry. my country's Panxi-Xichang region is rich in vanadium-titanium magnetite resources. Its vanadium and titanium are present in the form of vanadium-titanium magnetite in polymetallic symbiotic deposits, and are accompanied by a small amount of valuable elements such as cobalt, chromium, and copper. Panzhihua City is a world-renowned vanadium-titanium capital. Due to the characteristics of resource endowment, about 50% of the titanium in vanadium-titanium magnetite enters the blast furnace with the iron concentrate after ore dressing. In the ironmaking process, almost all of the titanium enters the slag phase, forming titanium iron slag (blast furnace slag) with a titanium content of about 18% to 26%. In addition to a small amount used as concrete filler, the blast furnace slag accumulated over decades has piled up like a mountain, and is still increasing by millions of tons every year, causing environmental pollution and low titanium resource utilization. After decades of scientific and technological research, the problem of its utilization has not been solved. It is an urgent practical problem to study the selective extraction and recovery of valuable components in blast furnace slag and use the leached slag enriched with TiO2 as raw material to produce titanium dioxide. The mature technology for the existing wet production of titanium dioxide is the sulfuric acid method titanium dioxide production technology, and the hydrochloric acid method titanium dioxide production technology is being developed. The titanium raw materials for the production of sulfuric acid method titanium dioxide and hydrochloric acid method titanium dioxide are mainly acid-soluble titanium slag and ilmenite concentrate. The decomposition acids used are sulfuric acid and hydrochloric acid, respectively. The acid decomposes the titanium-containing minerals to obtain titanium oxysulfate, titanium sulfate mixed solution and titanium oxychloride solution, respectively. Other acid-soluble impurities are decomposed into soluble sulfates and chlorides, such as divalent iron salts, calcium salts, magnesium salts, etc. Undecomposed minerals are mixed in the solution in the form of solid impurities, which can be removed by filtering. The solution is called titanium liquid. The titanium liquid is subjected to the process of impurity removal, concentration increase, hydrolysis to prepare hydrated titanium dioxide, filtration, washing, calcination, post-treatment, etc. to obtain pigment-grade titanium dioxide. However, the production of titanium dioxide by sulfuric acid process has the disadvantages of large acid consumption, long production process, high cost and great environmental pollution. At present, there are literatures and patent reports on the use of sulfuric acid to decompose titanium dioxide ferro slag to prepare titanium dioxide. In addition to the inherent disadvantages of sulfuric acid process titanium dioxide production, the dissolution of part of silicon in the leaching process will produce colloids, which makes it difficult to separate solids and liquids. For the literatures and patent reports on the decomposition of titanium dioxide ferro slag by hydrochloric acid to prepare titanium-rich slag or titanium dioxide, the extraction-stripping separation and recovery steps of calcium, magnesium, aluminum, silicon, chromium and iron or the distribution chemical precipitation separation steps are too cumbersome, the process is too long, the pollution is large, and it is difficult to achieve industrialization. Summary of the invention

[0003] The main technical problem solved by the present invention is to provide a method for preparing primary titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag (blast furnace slag) with hydrochloric acid. The method can utilize vanadium-titanium magnetite ironmaking slag to produce rutile titanium dioxide for pigment, thereby improving the resource utilization rate of titanium in vanadium-titanium magnetite, expanding the application field of by-products, and solving the environmental protection and resource waste problems caused by the current storage of vanadium-titanium magnetite ironmaking slag.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is:

[0005] According to the mineral coating characteristics of the vanadium-titanium magnetite ironmaking slag raw material, the decomposed material of the vanadium-titanium magnetite ironmaking slag used is a fine material that has been pre-activated and ground by vertical mills, stirred mills, etc. Due to the lattice defects and crystal transformation, amorphization of mineral particles during the mechanical activation process, and the breakage of surface chemical bonds to produce unsaturated groups, free ions and electrons, new surfaces are generated, resulting in lattice defects, which leads to an increase in the internal energy of the mineral crystal, an unstable chemically active state, and makes many reactions that cannot occur under normal pressure and room temperature possible. Compared with ordinary titanium iron slag powder, it has high surface energy properties and easy acid hydrolysis performance. The particle size of the acid-hydrolyzed titanium iron slag raw material is controlled to D max <38μm (400 mesh).

[0006] The activated vanadium-titanium magnetite ironmaking slag is leached at room temperature and pressure using a dilute hydrochloric acid solution with a hydrochloric acid concentration of 48-55g / L to selectively decompose the easily hydrochloric acid-decomposable compounds of impurity elements such as calcium, magnesium, aluminum, chromium and iron, and dissolve them into the acid solution in the form of chloride salts. TiO2 and Si are enriched in the leached slag. Solid-liquid separation is performed to obtain a first-stage leaching solution and a first-stage acid leaching slag with a TiO2 content greater than 40%. When the total chloride salt concentration in the first-stage leaching solution is lower than 400g / L, return to the first-stage acid leaching process and add hydrochloric acid to a free hydrochloric acid concentration of 50-55g / L, which is used as a first-stage dilute acid leaching leaching agent for the vanadium-titanium magnetite ironmaking slag;

[0007] The present invention aims to effectively extract titanium from vanadium-titanium magnetite ironmaking slag for use in the production of titanium dioxide, and use the byproduct as a raw material for cement, glass, ceramics, etc. Since calcium chloride has the characteristics of not being hydrolyzed and not being decomposed at high temperature, when the leachate reaching the chloride concentration requirement is spray-roasted to recover hydrochloric acid and prepare roasted slag, calcium will be present in the slag in the form of calcium chloride. Cement raw materials have strict requirements on chloride content and titanium content. Excessive chloride content in cement will seriously corrode steel bars and the like, and the concrete stability is poor. High TiO2 content in cement raw materials will seriously affect the hydration characteristics of cement clinker. In addition, CaSO4 has the characteristics of low solubility in acidic solutions and at higher solution temperatures. Therefore, sulfuric acid is quantitatively added to the first-stage leachate reaching the chloride concentration requirement according to the calcium ion concentration to perform calcium precipitation operation, and dihydrate gypsum and the first-stage leachate after calcium precipitation are obtained after solid-liquid separation; gypsum can be used as a raw material for cement clinker, and can also be used in industries such as building materials, papermaking and molds.

[0008] The regenerated acid produced by the chloride salt roasting system is used as the acid solution acid, and the hydrogen chloride gas produced by the hydrochloric acid analysis system or the chloride salt roasting system is introduced. The concentrated acid at normal pressure decomposes the first acid leaching residue of the vanadium-titanium magnetite ironmaking slag. Iron powder is quantitatively added to the acid solution to reduce Fe 3+ Cheng Fe 2+ , to ensure that there is a certain concentration of Ti in the acid solution after acid hydrolysis 3+ The solid-liquid separation produces the acid-hydrolyzed titanium liquid and the second-stage acid leaching residue. The second-stage acid leaching residue is a silicon-titanium composite material with a porous structure, which can be used as a fine filter aid for solid-liquid separation and washing in the production process.

[0009] The acid-hydrolyzed titanium liquid is mixed with the first leaching liquid after calcium precipitation, and then evaporated and concentrated, and the condensed acid is recovered to obtain a concentrated titanium liquid that meets the hydrolysis conditions. The concentrated chloride salt solution is spray-roasted to regenerate hydrochloric acid and obtain a mixture powder of oxides such as aluminum, magnesium, chromium and iron, and the hydrochloric acid is recycled. The roasted slag can be used in cement production, and aluminum, magnesium and iron are important components of cement raw materials.

[0010] The concentrated titanium liquid is hydrolyzed, the solid and the liquid are separated, and the hydrolysis mother liquor is sent to the mother liquor concentration system. The mother liquor condensation acid is mixed with the titanium liquid concentrated condensation acid and used as the secondary washing acid to wash the hydrated titanium dioxide filter cake.

[0011] The concentrated mother liquor is sent to the mother liquor roasting workshop for roasting, and the washing acid after washing the hydrated titanium dioxide filter cake is used as the absorption liquid to produce the regenerated acid which is reused for the second stage concentrated acid leaching.

[0012] The washed and qualified hydrated titanium dioxide filter cake is calcined in a rotary kiln to obtain the primary rutile titanium dioxide powder.

[0013] The beneficial effects of the present invention are:

[0014] The comprehensive utilization of vanadium-titanium magnetite in Panxi area is realized, the utilization rate of titanium resources is improved, and the resource utilization rate of valuable components such as calcium, magnesium, silicon, aluminum, iron, and chromium in vanadium-titanium magnetite ironmaking slag is high, which expands the application field and increases the added value. Since vanadium-titanium magnetite ironmaking slag is mainly stored as waste slag at present, using it as a raw material for the production of hydrochloric acid titanium dioxide will greatly reduce the production cost of hydrochloric acid titanium dioxide. Hydrochloric acid is recycled and reused, and the production process is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 It is a schematic diagram of the method flow of the present invention. DETAILED DESCRIPTION

[0016] The preferred embodiments of the present invention are described in detail below so that the advantages and features of the present invention can be more easily understood by those skilled in the art, thereby making a clearer and more definite definition of the protection scope of the present invention.

[0017] Embodiments of the present invention include:

[0018] A method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid is designed to solve the problems of low utilization rate of titanium resources in Panxi vanadium-titanium magnetite, low utilization rate of vanadium-titanium magnetite ironmaking slag, large-scale stockpiling, and great safety and environmental protection pressure. The pre-activated and ground titanium-titanium magnetite ironmaking slag is used as a raw material, and low-concentration hydrochloric acid is used to selectively leach impurity elements such as calcium, magnesium, aluminum, chromium and iron in the vanadium-titanium magnetite ironmaking slag at normal pressure and room temperature, and the filtrate is added with sulfuric acid to precipitate calcium. The first-stage acid leaching slag is heated and leached with concentrated hydrochloric acid and HCl gas to prepare an acid-hydrolyzed titanium liquid, and the solid-liquid separation is performed to obtain a second-stage acid leaching slag. The acid-hydrolyzed titanium liquid and the calcium precipitation leaching liquid are combined and concentrated to recover the condensed acid. The concentrated titanium liquid is hydrolyzed, filtered, separated, washed, and calcined to obtain a primary product of rutile titanium dioxide. The hydrolysis mother liquor is concentrated to recover hydrochloric acid, and the concentrated hydrolysis mother liquor is spray-roasted to regenerate hydrochloric acid and obtain a mixed oxide powder of aluminum, magnesium, silicon, chromium and iron.

[0019] Example 1

[0020] In this embodiment, the titanium concentrate is Panzhihua vanadium-titanium magnetite ironmaking slag, TiO2: 22.23%, Fe: 1.72%, P: 0.01%, Ca: 19.87%, Mg: 5.64%, Si: 9.42%, Al: 5.93, S: 0.47%.

[0021] The vanadium-titanium magnetite ironmaking slag is ground to D max ≤150μm (100 mesh). Then use vertical mill for activation grinding, the particle size of the obtained vanadium-titanium magnetite ironmaking slag is D 98 <36μm, D max <38μm (400 mesh).

[0022] 700L of leaching acid (HCl: 50.20g / L) was added to a 1m 3 In the leaching pot, start stirring, then add 70 kg of activated vanadium-titanium magnetite ironmaking slag into the leaching pot, stir and mix, the mineral acid ratio (mass volume ratio) is 1:10. After 3 hours of natural stirring reaction.

[0023] Open the discharge valve of the leaching pot, start the leaching slurry pump, pump the leaching slurry in the leaching pot into the diaphragm filter press for filtration, and the filter cake is a first-stage vanadium-titanium magnetite ironmaking slag acid leaching filter cake. The filtrate is a first-stage leaching solution mixed with chloride salts of calcium, magnesium, aluminum, iron and chromium. The filter cake is washed clean with low-concentration hydrochloric acid (HCl: 51.37g / L), and the washing liquid is returned to the dilute acid storage tank and used as a first-stage leaching acid. The first-stage leaching solution with a total chloride salt concentration of less than 400g / L is pumped into the first-stage leaching dilute solution storage tank, and concentrated hydrochloric acid is added to the free hydrochloric acid concentration of 50-55g / L, and used as a low-concentration hydrochloric acid vanadium-titanium magnetite ironmaking slag first-stage acid leaching leaching agent to improve the chloride salt concentration and acid utilization rate.

[0024] Pump 670L of the first-stage leachate (CaCl2: 219.46g / L) into a 1m 3 In the calcium precipitation reactor, open the steam, heat to 60℃ by indirect heat exchange with the jacket, add 130L 50% sulfuric acid solution at a uniform speed under stirring to perform calcium precipitation operation, heat the system to 95-98℃ and keep warm for 1 hour to make the calcium sulfate precipitation complete and the particles grow. Pump the precipitated mixed slurry into the diaphragm filter press to separate the dihydrate gypsum from the mixed solution of aluminum, magnesium, chromium, iron and other chloride salts. Pump the first stage leachate after calcium precipitation into the intermediate storage tank of the first stage leachate after calcium precipitation. The dihydrate gypsum in the filter press is washed, unloaded and dried to obtain the dihydrate gypsum by-product.

[0025] Add 500L of acid (HCl: 360.60g / L) into a closed volume of 1m 3 Add 500kg of vanadium-titanium magnetite ironmaking slag primary acid leaching filter cake (solid content of 50%) into the acid hydrolysis reactor and start stirring. The slag-acid ratio (mass-to-volume ratio) is 1:1. Introduce the hydrogen chloride gas obtained by hydrochloric acid analysis, use the heat of solution of hydrogen chloride gas to heat the system to 90°C, and maintain the system temperature to increase the acidity of the system, and stir the acid hydrolysis for 2 hours. Maintain the free hydrochloric acid concentration of the acid hydrolysis reactor at more than 270g / L. Add 5.2kg of iron powder before the end of the acid hydrolysis, and stir to reduce Fe 3+ Cheng Fe 2+ , Ti 3+ The concentration is 1.9g / L, and the solution is purple. The acid hydrolysis tail gas generated during the acid hydrolysis process is condensed and absorbed by the hydrochloric acid produced by the hydrochloric acid analysis system.

[0026] The acid-hydrolyzed slurry is hot filtered, and the filtrate is the acid-hydrolyzed titanium liquid. The indicators of the acid-hydrolyzed titanium liquid are (HCl: 259.02g / L, TiO2: 139.20g / L, Fe: 15.27g / L). The filter cake is washed clean with low-concentration hydrochloric acid (HCl: 51.37g / L), and the washing liquid is returned to the dilute acid storage tank and used as a first-stage leaching acid. After the filter cake is flash-dried, it becomes a porous silicon-titanium composite material.

[0027] The acid-hydrolyzed titanium liquid and the first-stage leaching liquid mixture (HCl: 173.27g / L, TiO2: 91.86g / L, Fe: 23.60g / L) are sent to the single-effect vacuum distillation system, and the mixture is boiled and concentrated at low temperature under vacuum, with a concentration ratio of 70%. The concentrated titanium liquid is pumped to the concentrated titanium liquid storage tank, and the concentrated titanium liquid detection indicators (HCl: 220.50g / L, TiO2: 303.37g / L, Fe: 49.24 / L) are detected. The steam and HCl generated by evaporation are condensed by the condensation device to obtain the titanium liquid concentrated condensed acid (152.63g / L), which is pumped to the secondary washing acid storage tank.

[0028] In 1m 3 Add 15 liters of hot water to the hydrolysis pot, start stirring, and rotate at 30r / min. Add the preheated 85 liters of concentrated titanium liquid to the hydrolysis pot within 10 minutes, and a slight white turbidity will appear; continue to add 615 liters of concentrated titanium liquid to the hydrolysis pot, pass saturated steam to heat directly, heat to the hydrolysis liquid slightly boiling and keep warm for 30 minutes; keep warm regularly to ensure that the solid product of titanium generated by continuous hydrolysis - hydrated titanium dioxide (TiO2·2H2O) reaches the hydrolysis rate required by the process, and the hydrolysis rate reaches 99%, and the hydrolysis is completed. Add 100g of wood cellulose to the hydrolysis pot and stir evenly. Stop heating, open the discharge valve of the hydrolysis pot, pump the hydrolyzed hydrated titanium dioxide slurry into the diaphragm filter press for filtration, and pump the hydrolysis mother liquor into the hydrolysis mother liquor storage tank. The hydrogen chloride gas and water vapor generated during the hydrolysis process are pumped to the falling film absorption system for tail gas absorption treatment, and the generated clean condensed acid is pumped into the secondary wash acid storage tank.

[0029] Open the hydrolysis mother liquor storage tank, pump the hydrolysis mother liquor into the hydrolysis mother liquor concentration reactor, start the steam, heat it to boiling by indirect heat exchange with the jacket, concentrate it according to a concentration ratio of 30%, condense and recover the hydrolysis mother liquor condensed acid, pump it to the secondary wash acid storage tank, and pump the concentrated mother liquor to the concentrated mother liquor storage tank of the spray roasting section.

[0030] In the secondary wash acid storage tank, the hydrolysis mother liquor condensed acid is mixed with the titanium liquid concentrated condensed acid as the secondary wash acid, and the secondary wash acid is pumped into the diaphragm filter press to wash the hydrated titanium dioxide filter cake. After washing, the acid is pumped to the spray roasting section absorption acid storage tank. The filter press is depressurized and opened to release the hydrated titanium dioxide filter cake into the feed bin.

[0031] The outlet valve of the concentrated mother liquor storage tank is opened, and the concentrated mother liquor is sprayed into the roasting furnace, contacts with hot air at a temperature of 700-850℃, and reacts with O2 and H2O to decompose into H2O+HCl mixed gas+solid metal oxide. The absorption acid storage tank is opened, and the washing acid after washing the hydrated titanium dioxide filter cake is used as the absorption liquid of the falling film absorption system in the spray roasting section to produce regenerated acid, which is pumped into the regenerated acid storage tank for the second-stage concentrated acid leaching and the addition of hydrochloric acid to the leaching system. The concentration of the regenerated acid is 360.60g / L.

[0032] The rotary kiln speed of the rotary kiln is adjusted to maintain 0.3r / min, and the exhaust fan at the kiln tail is turned on. When the temperature at the kiln tail reaches about 350℃, the hydrated titanium dioxide filter cake is fed through the screw conveyor and sent to the kiln tail for calcination. The residence time of the material in the calcination rotary kiln is adjusted to be 7 hours. The first temperature zone is 350-760℃, with a residence time of 2.6 hours, to complete the adsorption water removal, crystallization water removal, deacidification and desulfurization process of hydrated titanium dioxide; the second temperature zone is 760-870℃, with a residence time of 2 hours, to complete the rutile crystal transformation process of titanium dioxide; the third temperature zone is 870-930℃, with a residence time of 2.4 hours, to complete the titanium dioxide particle growth process. The titanium dioxide powder calcined at about 930℃ output from the calcining rotary kiln head is transferred to the air-cooled rotary kiln through the unloading device of the lower end cover of the kiln body to cool down to 60℃. The primary rutile titanium dioxide powder is obtained without the need for adding crystal seeds and salt treatment. The particle size is 0.2-0.35μm, the rutile content is greater than 99%, and the titanium dioxide content is 99.85%. The rotary kiln tail gas is sprayed, washed and heat-exchanged by the Venturi concentrator, absorbed by the first and second falling films, and defogged by the electric demister. Samples are taken every hour according to the "Technical Standards for Semi-finished Products" and sent to the laboratory for testing.

[0033] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent process changes made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid, comprising the following steps: (1) Grind the vanadium-titanium magnetite ironmaking slag to D using a roller mill. max ≤150μm, and then activated by vertical mill, the obtained vanadium-titanium magnetite ironmaking slag fine material particle size is D 98 <36μm, D max <38μm;(2) using dilute hydrochloric acid solution to leach the activated vanadium-titanium magnetite ironmaking slag at normal pressure to achieve selective leaching of impurity elements including calcium, magnesium, aluminum, chromium and iron, and separating the solid and liquid to obtain a first-stage leaching solution and a first-stage acid leaching residue;(3) when the total chloride concentration of the first-stage leaching solution is lower than 400g / L, returning to the first-stage acid leaching process and adding hydrochloric acid to a free hydrochloric acid concentration of 50-55g / L, as a first-stage dilute acid leaching leaching agent for vanadium-titanium magnetite ironmaking slag;(4) adding sulfuric acid to the first-stage leaching solution according to the calcium ion concentration to precipitate calcium, and after solid-liquid separation, obtaining dihydrate gypsum and a first-stage leaching solution after precipitating calcium;(5) adding concentrated hydrochloric acid as acid hydrolysis acid and HCl gas to heat and intensify the decomposition and washing of the first-stage acid leaching residue, and adding a small amount of iron powder before the end of acid hydrolysis to reduce Fe 3+ Cheng Fe 2+ , solid-liquid separation to obtain acid-hydrolyzed titanium liquid and second-stage acid leaching residue; the acid-hydrolyzed acid is the regenerated acid produced by the chloride salt roasting system, and the HCl gas is the HCl gas produced by the hydrochloric acid analysis system or the chloride salt roasting system; the free hydrochloric acid concentration of the acid-hydrolyzed reactor is maintained at 270 g / L or more, and the acid-hydrolyzed tail gas generated during the acid-hydrolyzed process is condensed and absorbed by the hydrochloric acid produced by the hydrochloric acid analysis system; (6) the acid-hydrolyzed titanium liquid is mixed with the first-stage leaching liquid after calcium precipitation, and then evaporated and concentrated, and the condensed dilute hydrochloric acid is recovered to obtain a concentrated titanium liquid that meets the hydrolysis conditions; (7) the concentrated titanium liquid is hydrolyzed to obtain hydrated titanium dioxide, which is filtered and washed, and the hydrated titanium dioxide filter cake is calcined to obtain the primary product of titanium dioxide for pigment, and the hydrolysis mother liquor is concentrated and spray-roasted to produce magnesium-aluminum-iron oxide slag; The first-stage acid leaching residue is cleaned with low-concentration hydrochloric acid with a hydrochloric acid concentration of 48-55g / L, and the washing liquid is returned to the dilute acid storage tank to be used as the first-stage leaching acid; the second-stage acid leaching residue is flash-dried to obtain a porous silicon-titanium composite material.

2. The method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite iron-smelting slag with hydrochloric acid according to claim 1, wherein the activated vanadium-titanium magnetite iron-smelting slag is leached in a dilute hydrochloric acid solution at normal pressure to selectively decompose the hydrochloric acid-decomposable compounds of calcium, magnesium, aluminum, chromium and iron impurity elements, and dissolve them in the acid solution in the form of chloride salts; solid-liquid separation is performed to obtain a first-stage acid leaching slag with a TiO2 content greater than 40%.

3. According to the method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid as described in claim 2, the supplementary hydrochloric acid is the dilute hydrochloric acid obtained by condensation in step (6).

4. The method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite iron-smelting slag with hydrochloric acid according to claim 1, wherein in step (2), a dilute hydrochloric acid solution with a hydrochloric acid concentration of 48-55 g / L is used to leach the activated vanadium-titanium magnetite iron-smelting slag at normal pressure and temperature.

5. The method for preparing primary titanium dioxide for pigment by decomposing vanadium-titanium magnetite ironmaking slag with hydrochloric acid according to claim 1, wherein the mass volume ratio of the mineral acid to the acid is 1:8-1:12, and the reaction is stirred.

6. According to the method for preparing a primary product of titanium dioxide for pigment by decomposing vanadium-titanium magnetite iron smelting slag with hydrochloric acid as described in claim 1, in step (7), the hydrolysis mother liquor is concentrated and then spray-roasted to produce regenerated acid, and the regenerated acid is used for two-stage concentrated acid leaching and adding hydrochloric acid to the leaching system, and the regenerated acid concentration is 270-380 g / L.